Draft Five Year Plan 1978-83 Panchayats Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
The total outlay for the Fifth Plan was approximately Rs. 4.98 Crores. the Plan ceiling for the Sixth Plan is Rs. 2265.29 lacs considering the fact that Government have announced that great importance should be paid to rural areas and to local government institutions. To ensure that the basic self governing institutions are able to discharge their duties satisfactorily, secretarial assistance is a basic necessity.
Government of Madhya Pradesh, Planning, Economics and Statistics Department